Design, Fabrication and Flight Demonstration of a Remotely Controlled Airship for Snow Scientists - Pant,Rajkumar Sureshchandra (2014)
ABSTRACT: A remotely controlled airship was designed, fabricated and demonstrated within a tight timespan of under a month after receiving the go-ahead. The main design requirement for this airship was to be able to operate from a Helipad located at an altitude of 6,572 feet AMSL under ISA+20 deg.C. The images of the terrain below were recorded during the flight and transmitted in real-time to a ground based system using an onboard telemetry system. The paper describes the methodology followed for sizing of the envelope and key components of the airship, and the procedure followed for in-house fabrication and testing. The major issues that cropped up during the operation of the airship in harsh weather conditions of rain and mild snow, as well as at night, are also highlighted. The demonstration established the efficacy of remotely controlled airships for aerial photography and data collection by snow scientists.